Optimal Human Functioning Requires Exercise Across the Lifespan: Mobility in a 1g Environment Is Intrinsic to the Integrity of Multiple Biological Systems - Hart, David A.; Zernicke, Ronald F. (Frontiers in Physiology, 2020)
It is widely acknowledged that achieving and maintaining a healthier lifestyle can be enhanced through regular participation in sport and physical activity. Coevally, a growing number of health professionals regard exercise as a legitimate intervention strategy for those who have lost their health. Exercise has been shown to be effective for overweight or obese individuals, who are at risk to lose their health due to development of type II diabetes, cardiovascular disease, as well as, infiltration of muscles, bone and other organs with fat, so it can be considered medicine. However, exercise and associated mobility likely also have a strong prevention component that can effectively contribute to the maintenance of the integrity of multiple biological systems for those who do not have overt risk factors or ongoing disease. While prevention is preferred over intervention in the context of disease, it is clear that exercise and associated mobility, generally, can be an effective influence, although overtraining and excessive loading can be deleterious to health. The basis for the generally positive influence of exercise likely lies in the fact that many of our physiological systems are designed to function in the mechanically dynamic and active 1g environment of Earth (e.g., muscles, cartilage, ligaments, tendons, bones, and cardiovascular system, and neuro-cognitive function), and nearly all these systems subscribe to the “use it or lose it” paradigm. This conclusion is supported by the changes observed over the more than 50 years of space flight and exposure to microgravity conditions. Therefore, the premise advanced is: “exercise is preventative for loss of health due to age-related decline in the integrity of several physiological systems via constant reinforcement of those systems, and thus, optimal levels of exercise and physical activity are endemic to, essential for, and intrinsic to optimal health and wellbeing.”